Musical Activities, Prosocial Behaviors, and Executive Function Skills of Kindergarten Children. (December 2021) - Ilari, Beatriz; Helfter, Susan; Huynh, Tina; Bowmer, Alice; Mason, Kathryn; Knight, Julian; Welch, Graham
Prosocial behaviors and executive function are staples of child development. Engagement in music has been associated with enhanced prosocial behaviors and executive function skills in children and youth. Yet, research concerning the role of formal music programs in the development of these important behaviors and skills remains elusive. The aim of this exploratory study was to investigate the role of a 5-week music program on prosocial behaviors (instrumental helping and sharing) and executive function skills (cognitive flexibility and working memory/inhibition control) of 103 kindergarten children from two public schools in a large urban center in the United States, serving predominantly Latinx children from underserved communities. Our data suggested that the short music program positively influenced children's cognitive flexibility, but not working memory, nor prosocial skills (sharing and helping). Findings are discussed in light of earlier studies, methodological issues, and limitations, and in relation to developmental and cultural issues surrounding child participants. Implications for future research and practice are outlined.